The Influence of Leadership-Member Exchange (LMX), Motivation and Continuity Commitment on Increasing the Work Productivity of State Vocational School Teachers in the City of Central Jakarta - Silitonga, Dikson; Sihotang, Hotmaulina; Murniarti, Erni (Sahabat Publikasi, 2024)
The measure of teachers' effectiveness and efficiency while doing their duties and responsibilities during the learning process is teacher productivity. Despite their location are close to the central of power, close to the source of policies, participate regularly in any competency training, and being equipped with better facilities, the productivity of teachers in Central Jakarta's municipality remains make apprehensive. This case indicates the need for evaluation and efforts to improve teacher's productivity continuously , which at the end will give positive impact the quality of education on the whole. This study aims to analyze the influence of Leadership-Member Exchange (LMX), motivation, and Continuance Commitment both partially and simultaneously on the productivity of public vocational schools teachers in Central Jakarta. Data were collected using a questionnaire distributed to 100 public vocational school teachers in Central Jakarta as the sample (respondents). Through a quantitative research method with a multiple regression analysis approach, the results indicate that LMX, motivation, and Continuance Commitment have a positive and significant impact on teacher productivity. Simultaneously, these three variables mutually support, leading to an overall increase in productivity. Based on these findings, it is recommended that schools need to enhance the quality of relationships between leaders and teachers and create a motivating work environment to support the achievement of optimal learning outcomes. This research is expected to provide insights for policymakers in formulating human resource development strategies in the education sector